2022
DOI: 10.1088/1748-9326/ac6435
|View full text |Cite
|
Sign up to set email alerts
|

Climate change will increase aflatoxin presence in US Corn

Abstract: The impacts of climate change on agricultural production are a global concern and have already begun to occur (1, 2), with major drivers including warmer temperatures and the occurrence of extreme weather events (3-8). An important dimension of the climate change-crop yield relationship that has often been overlooked in the empirical literature is the influence that warming temperatures can have on plant damage arriving through biotic channels, such as pest infestation or fungal infection (5). Aflatoxins are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…As many hybrids had very low or high to very high toxin contamination under the same environmental conditions, it is clear that, without knowing the resistance classification of the hybrid, its toxin behavior can hardly be forecasted. The forecasts shows higher toxin contamination in the northern hemisphere [ 35 , 37 , 42 , 84 , 85 ]. As the differences in hybrid resistance are very large in artificial inoculation tests [ 48 , 52 , 53 ] and also at natural infection and contamination verify this hypothesis, the combination of the two test regimes can lead to a decrease in toxin contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As many hybrids had very low or high to very high toxin contamination under the same environmental conditions, it is clear that, without knowing the resistance classification of the hybrid, its toxin behavior can hardly be forecasted. The forecasts shows higher toxin contamination in the northern hemisphere [ 35 , 37 , 42 , 84 , 85 ]. As the differences in hybrid resistance are very large in artificial inoculation tests [ 48 , 52 , 53 ] and also at natural infection and contamination verify this hypothesis, the combination of the two test regimes can lead to a decrease in toxin contamination.…”
Section: Discussionmentioning
confidence: 99%
“…We should not forget that the forecasting refers to the preharvest toxin contamination. As A. flavus and F. verticillioides need a higher optimum temperature than the ruling weather conditions secured in middle and western Europe, warmer and dryer summer conditions will increase the risk of aflatoxin and fumonisin contamination [ 36 , 37 ]. The different forecasting models [ 35 , 38 , 39 , 40 , 41 , 42 ] do not consider the resistance of the hybrids but use only the increasing temperatures and other non-plant traits.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging reports on the GCC demonstrated that GW has begun to occur but the empirical data on how GW might affect crops yield is markedly overlooked ( 62 ). Strategically, GW and GCC might alter the distribution of plant pests and diseases, resulted in a significant damage to crop production.…”
Section: The Upcoming Gcc and Future Afs Contamination Risksmentioning
confidence: 99%
“…In this regard, Yu et al reported that global temperature modification has an impact on the prevalence of AFs contaminants ( 62 ). According to the given model for simulation of AFs occurrence based on corn phenology, it is believed that some corn grown US states will experience an increased level of AFs occurrence by 2031–2040 ( 62 ).…”
Section: The Upcoming Gcc and Future Afs Contamination Risksmentioning
confidence: 99%
See 1 more Smart Citation